Updated Understanding of the Crosstalk Between Glucose/Insulin and Cholesterol Metabolism - Xiao, Xuan; Luo, Yonghong; Peng, Daoquan (Frontiers in Cardiovascular Medicine, 2022)
Glucose and cholesterol engage in almost all human physiological activities. As the primary energy substance, glucose can be assimilated and converted into diverse essential substances, including cholesterol. Cholesterol is mainly derived from de novo biosynthesis and the intestinal absorption of diets. It is evidenced that glucose/insulin promotes cholesterol biosynthesis and uptake, which have been targeted by several drugs for lipid-lowering, e.g., bempedoic acid, statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. Inversely, these lipid-lowering drugs may also interfere with glucose metabolism. This review would briefly summarize the mechanisms of glucose/insulin-stimulated cholesterol biosynthesis and uptake, and discuss the effect and mechanisms of lipid-lowering drugs and genetic mutations on glucose homeostasis, aiming to help better understand the intricate relationship between glucose and cholesterol metabolism.